The effect of excessive fat tissue on the measure of bone mineral density by dual X‐ray absorptiometry: the impact of substantial weight loss following sleeve gastrectomy. (24th July 2019) - Maïmoun, Laurent; Mariano‐Goulart, Denis; Jaussent, Audrey; Lefebvre, Patrick; Picot, Marie‐Christine; Mahadea, Krishna; Boudousq, Vincent; Fouillade, Clémence; Nocca, David; Ben Bouallègue, Fayçal
Summary: Purpose: Dual‐energy X‐ray absorptiometry (DXA) is used in clinical routine to determine areal bone mineral density (aBMD). However, it is not clear whether excessive fat mass or substantial weight loss modify the aBMD measurements. The aim of this study was to evaluate the effect of soft tissue composition on aBMD measured by DXA using a clinical model (i.e. sleeve gastrectomy: SG) that induces substantial body weight loss. Methods: Areal bone mineral density and body composition (fat mass: FM and lean tissue mass: LTM) were determined by DXA in 41 obese patients (33 women, 80.5%) just before SG and 1 month later. Results: One month after SG, mean weight loss was −9.8 ± 2.6 kg, with a significant decrease in LTM and FM (kg) ranging from −7.3% to −9.5%. The relative variation in aBMD was increased at the lumbar spine (2.45 ± 3.44%) and decreased at the hip (−1.47 ± 2.28%), whereas no variation was observed for the whole body and radius. The variation in aBMD at the lumbar spine was inversely correlated with variations in weight, whole‐body FM and trunk FM, but not LTM. Conclusion: This study shows evidence of a potential effect of body composition, particularly FM, on aBMD. However, given the modest change in aBMD, which was close to the precision error of aBMD measurements, it appears that significant weight loss does not have a clinically significant impact on the evaluation of aBMD using DXA.